The roles of outlet density and norms in alcohol use disorder. (1st June 2015) - Ahern, Jennifer; Balzer, Laura; Galea, Sandro
Highlights: We examine the relations of outlet density and norms with alcohol use disorder. A new targeted minimum loss-based estimator for rare outcomes is applied. Both neighborhood exposures have substantial relations with alcohol use disorder. There is no additive interaction between outlet density and norms. Abstract: Background: Alcohol outlet density and norms shape alcohol consumption. However, due to analytic challenges we do not know: (a) if alcohol outlet density and norms also shape alcohol use disorder, and (b) whether they act in combination to shape disorder. Methods: We applied a new targeted minimum loss-based estimator for rare outcomes (rTMLE) to a general population sample from New York City ( N = 4000) to examine the separate and combined relations of neighborhood alcohol outlet density and norms around drunkenness with alcohol use disorder. Alcohol use disorder was assessed using the World Mental Health Comprehensive International Diagnostic Interview (WMH-CIDI) alcohol module. Confounders included demographic and socioeconomic characteristics, as well as history of drinking prior to residence in the current neighborhood. Results: Alcohol use disorder prevalence was 1.78%. We found a marginal risk difference for alcohol outlet density of 0.88% (95% CI 0.00–1.77%), and for norms of 2.05% (95% CI 0.89–3.21%), adjusted for confounders. While each exposure had a substantial relation with alcohol use disorder, there was no evidence of additive interaction between the exposures. Conclusions: Results indicate that the neighborhood environment shapes alcohol use disorder. Despite the lack of additive interaction, each exposure had a substantial relation with alcohol use disorder and our findings suggest that alteration of outlet density and norms together would likely be more effective than either one alone. Important next steps include development and testing of multi-component intervention approaches aiming to modify alcohol outlet density and norms toward reducing alcohol use disorder.